Kesiapan Masyarakat Dalam Transformasi Menuju Desa Wisata Berbasis Community-Based Tourism - Pujiati, Heri Roh; Nugroho, Ricardho Dhaniel (Jurnal Komunikasi Pemberdayaan, 2026)
This study aims to analyze the readiness of the community of Wotawati Hamlet, Pucung Village, Girisubo Subdistrict, Gunungkidul Regency, in transforming into a Community-Based Tourism (CBT)-based tourist village. This research employs a descriptive qualitative approach to examine community readiness in the transformation process, using interviews, observations, and documentation, which are analyzed through the Miles and Huberman interactive model. The results show that community readiness is progressive but remains at a strengthening stage. This is indicated by the establishment of a tourism village working group supported by organizational bylaws (AD-ART) and management synergy through the Village-Owned Enterprise (BUMKal), the presence of two certified tour guides, and community participation in training programs related to guiding, homestay management, and micro, small, and medium enterprises (MSMEs). In addition, economic impacts have begun to emerge since 2023 through collectively managed parking and homestay revenues. Government support through the Village Budget (APBKal), Regional Financial Assistance (BKK), the Special Fund, and the development of a participatory master plan has further strengthened the transformation process. However, several challenges remain, including limited human resources among tourism actors, the absence of an entrance fee system, limited infrastructure access, and uneven community participation.Overall, community readiness is at an early development stage, with the potential to evolve into inclusive and sustainable CBT-based tourism village governance.